Sustainable Tall Green Building-Context Approaching Bangladesh - Ferdousi, Jannat Ara; Gupta, Bijoy Dash (IJRDO - Journal of Mechanical And Civil Engineering, 2017)
Bangladesh is a member of D-8 (Developing 8) countries in the world. But one of the problem is that it is a denselypopulated country. The population of this country has been increased at such a rate over the past few years that development plansfor the country by the government of Bangladesh has undergone many tremendous transformations. Especially in the urban area ishighly populated, but the amount of land is relatively very which has put severe pressure on the ecosystem of the urban life. Theincreased population has impacted the ecosystem of densely populated cities like Dhaka, Chittagong and Narayanganj. Thechanges in the population were paralleled by the real estate construction and housing industries. Dhaka, Chittagong, Narayanganjare some of the most polluted cities in Bangladesh. This is why sustainable green building-context is approaching Bangladesh.